Lecturer Eye Contact on the Students’ English Learning Motivation: Motivated or Demotivated - Maemuna Muhayyang; Geminastiti Sakkir; Amra Ariyani; Syamsiarna Nappu (EduLine: Journal of Education and Learning Innovation, 2023)
This study aims to describe the effect of lecturer eye contact on student learning motivation and the students’ perception on it during their interaction in EFL classroom. It employs a descriptive method in cluster random sampling taking 30 students of English Education class. The data sources of this study were observation, questionnaire, and interview and analyzed descriptively. The observation results that students are more likely to pay attention to the material, more enthusiastic in learning and more respectful to the lecturers having and keeping an eye contact in the teaching and learning process. The result of the questionnaire shows that the lecturer eye contact significantly affects the students’ learning motivation indicated by the mean score of the questionnaire, that is 3.71 falling into high category. These two findings are supported by the data gained from the interview in which most students argued that lecturer eye contact has many positive impacts on their learning. An excessive eye contact of the lecturer to the students, however, can become a hindrance to draw students’ focus on the materials presented. Therefore, the lecturer eye contact to nurture students’ learning motivation should be considerably sufficient and not excessive.